Students of the Bible in 4th and 5th Century Syria Seats of Learning, Sidelights and Syriacisms. - Lehmann, Henning (Santa Barbara : Aarhus University Press, 2008)
A number of prolific writers were active in the Syrian Church of the 4th and 5th centuries. However, in some cases these writers are only accessible by virtue of sidelights thrown e.g. from Armenian and Latin translations (as is the case with "Eusebius of Emesa"); or, their works may be hidden under false attributions in Greek manuscripts (eg in: "Pseudo-Chrysostomica"--In fact belonging to "Severian of Gabala"); or, their relationship to the Syriac language and culture may be misrepresented in modern research (as for "Theodoret of Cyrrhus"). Since the 1.
Description based on print version record.
Keywords: Religion; Eusebius, -- Bishop of Emesa, -- ca. 300-ca. 359 -- Theology; Severian, -- of Gabala, -- fl. 398-408 -- Theology; Theodoret, -- Bishop of Cyrrhus -- Theology; Bible -- Study and teaching -- Syria -- History; Bible -- Criticism, interpretation, etc. -- History -- Early church, ca. 30-600.; Bible -- Criticism, interpretation, etc. -- History -- Syrian Church; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Electronic books